2011
DOI: 10.1128/cvi.00333-10
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell-Mediated Immune Responses in Patients with Recurrent Herpes Simplex Virus Type 2 Meningitis

Abstract: The clinical picture of herpes simplex virus type 2 (HSV-2) infection includes genital blisters and less frequently meningitis, and some individuals suffer from recurrent episodes of these manifestations. We hypothesized that adaptive and/or innate immune functional deficiencies may be a major contributing factor in susceptibility to recurrent HSV-2 meningitis. Ten patients with recurrent HSV-2 meningitis were studied during clinical remission. For comparison, 10 patients with recurrent genital HSV infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
6
1
1
Order By: Relevance
“…Only scarce data are available on systemic HSV-specific T cell-mediated responses in the blood of patients with recurrent GH. A study of CD4+ T cell-mediated responses after ex vivo stimulation with HSV antigens did not demonstrate significant differences among patients with recurrent GH-and HSV-seropositive healthy controls [6]. In this study, the only significant difference in HSV-specific peripheral CD4+ T cell response was found between recurrent GH and HSV meningitis.…”
Section: Introductioncontrasting
confidence: 73%
“…Only scarce data are available on systemic HSV-specific T cell-mediated responses in the blood of patients with recurrent GH. A study of CD4+ T cell-mediated responses after ex vivo stimulation with HSV antigens did not demonstrate significant differences among patients with recurrent GH-and HSV-seropositive healthy controls [6]. In this study, the only significant difference in HSV-specific peripheral CD4+ T cell response was found between recurrent GH and HSV meningitis.…”
Section: Introductioncontrasting
confidence: 73%
“…In agreement with this, our earlier studies of the immune responses in patients with recurrent genital HSV-2 infection and HSV-2 meningitis clearly showed a strong HSV-specific T cell reactivity and a higher innate function compared with healthy controls. The cytokines IL-12, TNF-α and IL-10 were particularly elevated in the patients with meningitis, suggesting that repeated exposures of HSV to the adaptive immune system provide a response with a Th1 profile 26. It would be interesting to combine a study like ours with monitoring HSV shedding to further illuminate the nature of the specific T cell responses and its significance for controlling HSV reactivation and viral shedding as well as the development of HSV-induced lesions.…”
Section: Discussionmentioning
confidence: 91%
“…Franzen-Röhl et al (6) showed that, contrary to their hypothesis, patients with recurrent HSV-2 meningitis have a stronger HSV-specific cell-mediated immune response compared with patients with recurrent genital HSV-2 infections and healthy seropositive persons. RBLM patients were found to have increased expression of Toll-like receptors (TLRs) and increased interferon (IFN)-α and specific T cell responses, suggesting that the proinflammatory state leads to a more severe clinical disease because of destruction of the blood-brain barrier, tissue remodeling, and vascular leakage (6). IgG1 and IgG3, which largely act against protein components such as tetanus and diphtheria toxin, mediate antibody-dependent cellular cytotoxicity important for clearance of bacterial and viral infections.…”
Section: Discussionmentioning
confidence: 90%